The survival of the conformist: social pressure and renewable resource management - Alessandro Tavoni; Maja Schlüter; Simon Levin (Fondazione Eni Enrico Mattei (FEEM), 2010)
This paper examines the role of pro-social behavior as a mechanism for the establishment and maintenance of cooperation in resource use under variable social and environmental conditions. By coupling resource stock dynamics with social dynamics concerning compliance to a social norm prescribing non-excessive resource extraction in a common pool resource (CPR), we show that when reputational considerations matter and a sufficient level of social stigma affects the violators of a norm, sustainable outcomes are achieved. We find large parameter regions where norm-observing and norm-violating types coexist, and analyze to what extent such coexistence depends on the environment.
Keywords: C73; Q20; D70; 330; Cooperation; Social Norm; Ostracism; Common Pool Resource; Evolutionary Game Theory; Replicator Equation; Agent-based Simulation; Coupled Socio-resource Dynamics